Comparison of Naive Bayes and Support Vector Machine Algorithms in Sentiment Analysis - Sela, Tiara; Sonita, Anisya (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2025)
Twitter is a social media platform that quickly spreads public opinion. The Ronald Tannur case, widely discussed on this platform, triggered various public reactions. This study aims to compare the Naive Bayes and Support Vector Machine (SVM) algorithms in analyzing netizens’ sentiment toward the case. The process includes data collection and text preprocessing, such as removing duplicates, cleaning, case folding, word normalization, stopword removal, tokenization, and stemming. The text is then transformed using TF-IDF. Sentiment classification is performed using both algorithms and evaluated through metrics like accuracy, precision, recall, F1-score, and AUC. The models are tested on three data split schemes: 90:10, 80:20, and 70:30. The results show that SVM with 90% training data provides the best performance, achieving 88.78% accuracy and 0.84 AUC, outperforming Naive Bayes, which only reached 71.29% accuracy and 0.77 AUC. This shows that SVM is more accurate in detecting sentiment on social media.Keywords : Sentiment Classification; Naive Bayes Algorithm; Support Vector Machine Algorithm; Twitter; Python AbstrakTwitter merupakan media sosial yang cepat menyebarkan opini publik. Kasus Ronald Tannur, yang banyak dibicarakan di platform ini, memicu beragam reaksi dari masyarakat. Penelitian ini bertujuan untuk membandingkan algoritma Naive Bayes dan Support Vector Machine (SVM) dalam menganalisis sentimen warganet terhadap kasus tersebut. Proses analisis mencakup pengumpulan data, praproses teks seperti penghapusan duplikat, pembersihan, case folding, normalisasi kata, penghapusan stopword, tokenisasi, dan stemming, lalu data ditransformasi menggunakan TF-IDF. Klasifikasi sentimen dilakukan menggunakan kedua algoritma dan dievaluasi dengan metrik seperti akurasi, presisi, recall, F1-score, dan AUC. Pengujian dilakukan pada tiga skema pembagian data latih dan uji, yaitu 90:10, 80:20, dan 70:30. Hasil menunjukkan bahwa SVM dengan rasio data latih 90% memberikan hasil terbaik dengan akurasi 88,78% dan AUC 0,84, melampaui Naive Bayes yang hanya mencapai akurasi 71,29% dan AUC 0,77. Ini menunjukkan bahwa SVM lebih akurat dalam mengenali sentimen di media sosial.